Semantic activation of phonetic radicals in Chinese. Issue 5 (28th May 2017) - Tsang, Yiu-Kei; Wu, Yan; Ng, Hezul Tin-Yan; Chen, Hsuan-Chih
ABSTRACT: The phonetic radical of a Chinese character is typically considered as a sublexical unit providing clues to pronunciation. This tradition was challenged by a previous study showing that the meanings of phonetic radicals affected character naming speed. Three experiments were conducted to further investigate this issue. Experiments 1 and 2 showed that the meanings of phonetic radicals could be activated in the primed character decision and semantic categorisation tasks, indicating that the semantic activation of phonetic radicals is robust in different tasks. Moreover, Experiment 1 also showed that the meanings of phonetic radicals could be as strongly activated as whole characters. Experiment 3 adopted a multi-prime procedure and showed that the semantic activation of phonetic radicals could be eliminated when a prior context was supportive to whole-character meanings. These results are discussed with reference to the nature of sublexical processing in Chinese and how context influences character recognition.